Risk of insolvency and return of shares: empirical analysis of Altman's Z-Score in the Peruvian mining sector between 2008 and 2018 - Lizarzaburu, Edmundo R. (2021)
This research pretends to evaluate the significance of the insolvency risk, referred by Altman's Z-Score, in the explanation of the historical return of the 7 most liquid mining companies listed in the Lima Stock Exchange based on a Market Return Model (MRM) under a cross-sectional approach. In this sense, daily data was collected from the S&P/BVL Peru Select index and the Peruvian 10-year Sovereign Bond between 2008-2018, approximated quarterly by the geometric average to homogenize them with the frequency of the Z. Thus, two central results were obtained: 1) The Z-Score, as an estimator of insolvency risk, is not valid to explain the behavior of the historical return of the shares, and 2) The Market Premium is statistically significant within the yield analysis. Also, contrary to the common literature, the results suggest the validity of Sharpe's conventional CAPM.